2000
DOI: 10.1097/00001756-200007140-00047
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotides block agonist-driven 45Ca2+ influx in chick embryo retinal explants

Abstract: AMPA (EC50 = 1.0 x 10(-6) M) and NMDA (EC50 = 1.3 x 10(-4) M) trigger 45Ca2+ influx in 13-day chick embryonic retinal explants. This agonist-driven cationic flux is specifically inhibited by typical competitive antagonists, such as 6,7-dinitroquinoxaline-2,3-dione (DNQX) and 2-amino-7-phosphonoheptanoate (AP7), respectively. Guanine nucleotides, with different degrees of phosphorylation, namely 5'-GMP, guanosine 5'-O-(2-thiodiphosphate) (GDPbetaS), guanosine 5'-O-(3-thiotriphosphate) (GTPgammaS) and 5'-guanyly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…7,8 These results add to the accumulated evidence on the antagonistic behavior of guanine nucleotides (GNs) at ionotropic glutamate receptors, in very diverse experimental setups, including agonist displacement, electrophysiological recording and neuroprotection paradigms. 7,8,[11][12][13][14][15][16][17][18][19][20] To further characterize the antagonistic behavior of GNs toward ionotropic glutamate receptors in chick retina we injected newborn chick retinal membrane microfragments into Xenopus oocytes and measured the effect of GNs on currents elicited by kainate under voltage-clamp conditions. This novel oocyte microinjection technique has been shown to result in a quick and efficient incorporation of foreign receptor channels into the oocyte membrane, in their own natural molecular environment, so that inward cationic current responses are readily recorded on exposure of the chimeric oocyte to the specific agonist.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…7,8 These results add to the accumulated evidence on the antagonistic behavior of guanine nucleotides (GNs) at ionotropic glutamate receptors, in very diverse experimental setups, including agonist displacement, electrophysiological recording and neuroprotection paradigms. 7,8,[11][12][13][14][15][16][17][18][19][20] To further characterize the antagonistic behavior of GNs toward ionotropic glutamate receptors in chick retina we injected newborn chick retinal membrane microfragments into Xenopus oocytes and measured the effect of GNs on currents elicited by kainate under voltage-clamp conditions. This novel oocyte microinjection technique has been shown to result in a quick and efficient incorporation of foreign receptor channels into the oocyte membrane, in their own natural molecular environment, so that inward cationic current responses are readily recorded on exposure of the chimeric oocyte to the specific agonist.…”
mentioning
confidence: 69%
“…T he ex vivo chick embryonic retinal preparation has won wide acceptance as a convenient and versatile model system for excitotoxicity and neuroprotection studies. [1][2][3][4][5][6][7][8][9][10] In this experimental context, we have recently shown that guanine nucleotides protect against kainate-and N-methyl-D-aspartate (NMDA)-induced damage, and block AMPA-and NMDA-driven 45 Ca 2ϩ influx, in 13-day chick embryonic retinal explants. 7,8 These results add to the accumulated evidence on the antagonistic behavior of guanine nucleotides (GNs) at ionotropic glutamate receptors, in very diverse experimental setups, including agonist displacement, electrophysiological recording and neuroprotection paradigms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Guanine nucleotides block agonist-driven Ca 2+ influx in chick embryo retinal explants [238]. RT-PCR studies revealed changes in the expression of P2X3 and P2X5 receptor mRNA at different postnatal stages, P23 to P210, of pigmented retinas [239].…”
Section: Retinamentioning
confidence: 98%
“…However, guanine-based purines can also be considered part of the purinergic system and they are released from neurons and/or glia both under basal conditions and after various types of stimulation, including stress conditions [1][2][3] . Thus, although traditionally guaninebased purines have been studied as modulators of intracellular processes, they can exert extracellular effects not related to their direct modulation of G proteins, including modulation of the glutamatergic activity [4][5][6][7][8][9][10][11][12][13] , behavioural effects 14,15 , and trophic effects on neural cells 16 . Some of the actions of the guanosine may be mediated intracellularly after its uptake, even if many trophic effects of guanine-based purines are not substantially affected by the nucleoside uptake inhibitors indicating that they are independent of intracellular mechanisms 17 .…”
Section: Theoretical Survey On Tautomerism Of Thioguanine Tautomers Bmentioning
confidence: 99%